The dominant themes in storytelling by entrepreneurs in small business enterprises in South Africa - ISA, REHEMA K. (My University, 2012)
The purpose of the research was to gain meaningful insights on the dominant themes of stories as told by entrepreneurs in the course of running their businesses. This research focussed on entrepreneurs of small and medium enterprises and varied in reach to entrepreneurs from services, manufacturing, construction and retail industries. It is less apparent what entrepreneurs of small business enterprises recount as the most significant story that they tell, the reasons why they tell it and the impact of the stories they tell. A significant proportion of the stories told were in the format accounts, telling of specific points in time of the business. The dominant theme for each entrepreneur was typically linked in many instances to what the literature available on the subject of storytelling in organisations documents. The narratives were analysed in three aspects, themes, forms and purpose the result of which were namely: • Purpose: the stories told by entrepreneurs were predominantly stories to create meaning, inform and to enhance knowledge around entrepreneurship • Themes: the stories told by entrepreneurs of their businesses were linked to the leader (themselves) and the role they have played in their businesses. • Forms: the forms of storytelling by the entrepreneurs being interviewed were predominantly accounts with the exception of two anecdotes. Although each entrepreneur found a story to tell, it was noted that most responded that they never considered what they were recounting as stories, but rather as statements of fact of what happened in their businesses. The main application of storytelling was never as a deliberate action or process but rather circumstantial opportunity to narrate. Stories remain in the domain of social interaction with the majority of stories circulated within the entrepreneur circles, friends and family. - III - While each entrepreneur had a unique tale, with common lessons and messages, in only three instances were the stories told used internally within the organisation. The main audience that the entrepreneurs told their stories to was other entrepreneurs. The richness in terms of the content, form and purpose of the stories told, their current application as evidenced by entrepreneurs of small and medium enterprises, indicates that storytelling in South Africa remains an untapped business tool.
MBA thesis - WBS
Keywords: Storytelling; Story telling; Small business enterprises; Entrepreneurs